Renewable Energy Sources: Engineering, Technology, Innovation ICORES 2017 (Springer Proceedings in Energy,, 2018)
This volume presents refereed papers based on the oral and poster presentations at the 4th International Conference on Renewable Energy Sources, which was held from June 20 to 23, 2017 in Krynica, Poland. The scope of the conference included a wide range of topics in renewable energy technology, with a major focus on biomass and solar energy, but also extending to geothermal energy, heat pumps, fuel cells, wind energy, energy storage, and the modeling and optimization of renewable energy systems. The conference had the unique goal of gathering Polish and international researchers' perspectives on renewable energy sources, and furthermore of balancing them against governmental policy considerations. Accordingly, the conference offered not only scientific sessions but also panels to discuss best practices and solutions with local entrepreneurs and federal government bodies. The Conference was jointly organized by the University of Agriculture in Krakow, the International Commission of Agricultural and Biosystems Engineering (CIGR), the Polish Society of Agricultural Engineering, AGH University of Science and Technology (Krakow), the Polish Society for Agrophysics under the patronage of the Rector of the University of Agriculture in Krakow, the Polish section of the Combustion Institute, and the Polish Chamber of Ecology.